2018
DOI: 10.32709/akusosbil.422221
|View full text |Cite
|
Sign up to set email alerts
|

Narsist Kişiliğin Makyavelist Davranışlara Etkisi: Kocaeli Üniversitesi Özel Güvenlik Öğrencileri Örneği

Abstract: Her insanın kişilik özellikleri farklıdır. Bireylerin karakterleri değişik faktörlere göre oluşmaktadır. Bu faktörlerden bazıları kişilik bozukluklarına neden olabilmektedir. Narsist kişilik her şeyin odağında kendisini görür. Bu kişilik yapısına sahip bireyler, iş yaşamında makyavelist davranışlara yatkınlık göstermektedirler. Bu çalışmanın amacı; narsist kişiliğin makyavelist davranışlara etkisini incelemektir. Kocaeli Üniversitesi Özel Güvenlik ve Koruma programında öğrenim gören öğrenciler araştırma evreni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
1
1
0
1
Order By: Relevance
“…It was found that there is a positive statistically significant relationship between the total score of Narcissism Personality Inventory and the Machiavellianism Scale. Similar results were found in the studies conducted [8,32]. It can be said that as the narcissistic personality level of students increases in higher education institutions, the Machiavellian personality level increases.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It was found that there is a positive statistically significant relationship between the total score of Narcissism Personality Inventory and the Machiavellianism Scale. Similar results were found in the studies conducted [8,32]. It can be said that as the narcissistic personality level of students increases in higher education institutions, the Machiavellian personality level increases.…”
Section: Discussionsupporting
confidence: 89%
“…Another factor that may be associated with narcissism is Machiavellianism. Uçkun et al found that there is a positive relationship between narcissistic admiration and Machiavellian behavior, the narcissistic personality affected the Machiavellian behavior [8]. Machiavellianism characterizes emotionally disconnected relationships, an interpersonal manipulative style, the desire to exploit others [9].…”
Section: Introductionmentioning
confidence: 99%
“…Alan yazında karanlık üçlü içerisinde yer alan makyavelizm (Paulhus ve Williams, 2002;Jakobwitz ve Egan, 2006;Jonason, Li, Webster ve Schmitt, 2009;Wai ve Tiliopoulos, 2012;Özsoy ve Ardıç, 2017;Bolelli, 2018;Tozar, 2019) narsizm ve psikopati ile de birlikte çalışılan bir kavramdır (McHoskey, 1995;Uçkun, Üzüm ve Uçkun, 2018;Murat ve Börü, 2019). Ayrıca makyavelizm etik (Singhapakdi, 1993;Güney ve Mandacı, 2009;Bitlisli ve Dinç, 2015), etik olmayan davranışlar (Vezir, 2017), sinizm (Özsoy, 2017), olumsuz durumları ifşa etme (Demirtaş ve Biçkes, 2014), örgütsel vatandaşlık davranışı (Becker ve Dan O'Hair, 2007) ve daha birçok kavram ile birlikte çalışılmıştır.…”
Section: Makyavelist Kişilik öZelliğiunclassified